TD-CFD-DPM Coupled method for multi-objective optimization of collision pollination parameters in hybrid rice seed production - Te Xi; Rongkai Shi; Huaiqu Feng; Bo Chen; Nian Li; Yongwei Wang; Jun Wang (Smart Agricultural Technology)
Abstracts: Elucidation of the pollen dispersal behavior during the production of hybrid rice seeds is imperative for the optimization of the pollination process and the promotion of mechanized pollination. This paper presents a multi-objective optimization method combining the TD-CFD-DPM (Transient Dynamics - Computational Fluid Dynamics - Discrete Phase Model) method and genetic algorithm for optimizing collisional pollination parameters for large-scale seed production of hybrid rice. The construction of a rice-air-pollen multiphase coupling model was undertaken to simulate the pollen diffusion and deposition process. This model was then combined with a response surface experimental design to construct an objective function, which was used to visualize the pollen movement trajectory and deposition distribution. The genetic algorithm was further utilized to optimize the pollination operation parameters. The feasibility of the model and the optimized parameters was verified by means of collaborative collision module experiments. The results demonstrated that the optimized parameter combinations exhibited satisfactory performance with regard to pollen dispersal distance and distribution uniformity. The pollen dispersal distances were all greater than 1.3 m The uniformity of pollen distribution was high, and its coefficient of variation was maintained below 80 %. The mean discrepancy between the calculated and experimental values of the optimized parameter combinations was found to be <6 %. This study offers both theoretical underpinnings and practical directives to advance the mechanized pollination theory and facilitate the mechanized pollination of hybrid rice for large-scale seed production.